Evaluation of serum transaminase level as diagnostic tool for assessing hepatic disease conditions among chronic hepatitis B patients in Bangladesh - Md Shaief, Fahmi; Alam, SM Sabbir; Alam, Md Shahinul; Yasmin, Mahmuda; Ahsan, CR; Jamalunnessa, - (Bangladesh Journal of Microbiology, 2018)
Chronic hepatitis B (CHB) is a major infectious disease which frequently involves liver injury and could be serious, even life threatening. Complications mainly include the development of chronic liver disease (CLD), cirrhosis, hepatocellular carcinoma (HCC), and liver failure. Liver function tests like determining the level of serum alanine aminotrasnferase (ALT), aspertate aminotransferase (AST) are orthodoxly used to assess the inflammatory activity and cirrhotic process in the liver. A total 2453 patients with an age range of 12-86 years with a positive HBsAg serostatus for more than six months was included in this study. Among them hepatic disease conditions were confirmed for 952 patients using visible symptoms, histological findings and precutaneous liver biopsy. Patients were examined for the serum ALT and AST level as biochemical markers, HBeAg and anti-Hbe level as serological markers, and HBV DNA level as molecular marker. In this study it was found that the probability to have a raised level of ALT and AST increases as the disease progresses from less severe to more severe conditions. Almost 80% of the CHB patients were documented to contain a raised level of ALT and the ratio was found to be increased to 93% for patients with CLD and 100% in patients diagnosed with HCC. For AST, elevated level was found for 61% of CHB patients without liver complication and 97% of CLD patients. Among CLD patients, 91.7% have raised level of both ALT and AST. And it was also found that the presence of serum HBe Ag and Anti HBe antibody have a significant relationship with raised level of serum ALT, and AST. Significant relations were also found for raised level of DNA with higher level of serum ALT and AST. This study shows that there is significant correlations of serum ALT, AST level with hepatic disease conditions and other diagnosing markers like serum HBe Ag, Anti-HBe antibody and HBV DNA level. Bangladesh J Microbiol, Volume 34 Number 1 June 2017, pp 39-42